Gender Equality in the Mirror Reflecting on Power, Participation and Global Justice - Fornalé, Elisa (Brill, 2022)
By taking an innovative perspective, Gender Equality in the Mirror aims to advance the debate on gender equalities and to engage with the complexities of their practical implications in everyday life. Through the voice of women who are contributing with their life and work to the pursuit of the collective task of inclusion, the volume develops an original analysis of the socio-economic and political dimension of gender parity to frame implementing pathways of aspirational human rights principles. Gender Equality in the Mirror explores these dimensions with the ultimate aim of raising broad awareness of the need to invest in women's empowerment for the construction of our society.